Complete mitochondrial genome of Nanjiang Yellow goat (Capra hircus). (3rd March 2016) - Li, Haijun; Meng, Xiangren; Zhang, Hao; Duan, Xiaoyue; Niu, Lili; Wang, Linjie; Li, Li; Zhang, Hongping; Wu, Hongda; Zhong, Tao
Abstract: Nanjiang Yellow goat ( Capra hircus ) is the first cultured mutton breed in China. In this study, the complete mitochondrial genome sequence of Nanjiang Yellow goat has been identified for the first time. The total length of the mitochondrial genome was 16, 639 bp, with the base composition of 33.54% A, 26.05% C, 13.11% G and 27.30% T. It contained 37 genes (22 transfer RNA genes, 2 ribosomal RNA genes, and 13 protein-coding genes) and a major non-coding control region (D-loop). Most of the genes have ATG initiation codons, whereas ND2, ND3 and ND5 start with ATA. The complete mitochondrial genome sequence of Nanjiang Yellow goat provides an important data set for further estimation on the phylogeographic structure of domestic goats.